Asset-Based Community Development: Program Inovasi Kampung Bantar - Bela, Hafizoh; Annshori, Muhammad; Marshalita, Mikyal (Matra Pembaruan: Jurnal Inovasi Kebijakan, 2024)
The Bantar village innovation program has been implemented since 2015. By 2021, the number of Bantar villages will have reached 710 in the city of Jambi. The aim of the program is to improve welfare through independent development amidst the minimal APBD. The government motivates the community by holding competitions to realize independent development while facing economic and social problems. This program will bring many benefits; however, in reality, only a few Bantar villages are sustainable out of the 710 Bantar villages spread across the city of Jambi. This anomalous phenomenon does not occur in RT 19, Paal Merah Village, District, Paal Merah, Jambi City. The Bantar village program in RT19 remains sustainable. Therefore, this article will focus on discussing the poverty factors of the Bantar village innovation program RT 19 Kampung Bersinar through the asset-based community development (ABCD) approach. Qualitative research design with a case study approach and data collection techniques in the form of observation, interviews, and documentation. As a result, internal factors, namely the role of the facilitator, become the main force in mobilizing society and, finding community assets or potential through the Discovery, Define, Dream, Design, and Destiny stages in line with the formation of human, social, cultural, political, ABCD approach, external factors should not be ignored to explain the phenomenon. l and financial capital. In the ABCD approach, external factors should not be ignored to explain the phenomenon. So, both internal and external factors are very important in realizing a sustainable Bantar village innovation program.